PENGARUH TANGGUNG JAWAB SOSIAL, KEBIJAKAN DIVIDEN, UKURAN PERUSAHAAN, PROFITABILITAS TERHADAP NILAI PERUSAHAAN - Kevin Jeonghun Yonathan Jeong; Augustpaosa Nariman (Jurnal Paradigma Akuntansi, 2023)
This study aims to determine the effect of corporate social responsibility, dividend policy, company size, and profitability on firm value in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2019 period. The sample was selected by purposive sampling method and the valid data were 46 companies. The data processing technique uses multiple regression analysis assisted by the software Eviews 11 for Windows and Google Sheets. The results of this study indicate that corporate social responsibility and dividend policy have a positive and insignificant effect on firm value. Firm size has no significant effect on firm value. Profitability has a positive and significant effect on firm value. The implication of this research is that the interests of corporate social responsibility, dividend policy, company size, and profitability will increase company value which is something that investors consider to invest.